Proximal Left Main Bronchus Resection–Reconstruction through Left Thoracotomy with Tracheal Traction - Imanishi, Naoko; Takenaka, Masaru; Hirai, Ayako; Tanaka, Fumihiro (The Thoracic and Cardiovascular Surgeon, 2018)
Surgical approach for resection–reconstruction of the proximal left main bronchus has been a matter of discussion. Through standard left thoracotomy, the proximal main bronchus close to the carina is not easily exposed. Accordingly, median sternotomy or right thoracotomy may be commonly employed, but the exposure and management of the distal left main bronchus may be difficult through the approach. Here, we present a left thoracotomy approach with traction of the trachea, which may easily allow excellent exposure of the proximal end of the left main bronchus and the carina.
Keywords: proximal left main bronchus; reconstruction; carinoplasty; tracheal traction; thoracotomy